The ameliorative effect of bergamot oil nano-emulsion in stressed rabbit bucks: Influence on blood biochemical parameters, redox status, immunity indices, inflammation markers, semen quality, testicular changes and the expression of HSPs genes - Sultan A.M. Saghir; Sulaiman M. Alnaimat; Saif M. Dmour; Ayat H. Al-Tarawni; Sameh A. Abdelnour; Ahmad F. Ahmeda; Ahmed H. Arisha; Mohammed F. Hawwal; Abdullah R. Alanzi; Ramzi A. Mothana; Ulrike Lindequist (Elsevier, 2023)
This work explored the activities of bergamot oil nano-emulsion (NBG) in modulating blood biochemical parameters, redox status, immunity indices, inflammation markers, semen quality, testicular changes and the expression of HSPs genes in stressed rabbit bucks. Twenty-four mature rabbit bucks (5 months) were randomly divided into three groups; control group (NBG0) received 1 ml of distilled water, while the other two groups received NBG orally at doses of 50 and 100 mg/kg (bw) twice a week. The present study's findings revealed that treated groups had lower values of total and direct bilirubin, triglyceride, lactate dehydrogenase, and creatinine compared with NBG0 group (p < 0.05). NBG100 group recorded the greatest of total protein, albumin, GPx, T3 and T4 values as well as the lowest values of uric acid, MDA, and indirect bilirubin. Both treated groups showed significantly reduced 8-OhDG, Amyloid A, TLR 4, while significantly increased nitric oxide, IgA, IgM, TAC, and SOD levels. Semen characteristics such as volume, sperm count, sperm motility, normal sperm, and vitality were significantly higher in the NBG100 group compared to the NBG50 and NBG0 groups, whereas sperm abnormalities and dead sperm were significantly reduced. HSP70, HSP72, and HSPA9 gene overexpression showed that testicular integrity was maintained after buck received oral doses of 50 or 100 mg/kg of NBG. Existing findings indicate that oral administration of NBG improves heat tolerance in rabbit bucks primarily as e result of its antioxidant and anti-inflammatory effects.